Pectoralis Major Onlay vs Interpositional Reconstruction Fistulation After Salvage Total Laryngectomy: Systematic Review and Meta-analysis. (May 2021) - Cabrera, Claudia I.; Joseph Jones, Alexander; Philleo Parker, Noah; Emily Lynn Blevins, Amy; Weidenbecher, Mark S.
Objective: To evaluate the difference in pharygocutaneous fistula (PCF) development between pectoralis major flap onlay and interpositional reconstructions after salvage total laryngectomy (STL). Data Sources: Medline, Cochrane, Embase, Web of Science, CINAHL, and ClinicalTrials.gov. Review Methods: A systematic review was performed during January 2020. English articles were included that described minor and major PCF rates after STL reconstructed with pectoralis major onlay or interposition. PCFs were classified as major when conservative therapy was unsuccessful and/or revision surgery was needed. Articles describing total laryngopharyngectomies were excluded. Meta-analyses of the resulting data were performed. Results: Twenty-four articles met final criteria amassing 1304 patients. Three articles compared onlay with interposition, and 18 compared onlay with primary closure. Pectoralis interposition demonstrated elevated odds ratio (OR) of PCF formation as compared with onlay (OR, 2.34; P < .001). Onlay reconstruction reduced overall (OR, 0.32; P < .001) and major (OR, 0.21; P < .001) PCF development as compared with primary pharyngeal closure alone. Data were insufficient to compare interposition against primary closure. Conclusions: This research shows evidence that pectoralis onlay after STL diminishes the odds of total and major PCF development. Pectoralis interposition reconstruction showed elevated odds of PCF formation as compared with pectoralis onlay.